Organic carbon promotes algae proliferation in membrane-aeration based bacteria-algae symbiosis system (MA-BA). (1st June 2020) - Zhang, Han; Gong, Weijia; Zeng, Weichen; Yan, Zhongsen; Jia, Baohui; Li, Guibai; Liang, Heng
Abstract: In the bacteria-algae (BA) system, the amount of oxygen produced by the algae is always insufficient for the organic carbon degradation, resulting in less inorganic carbon (IC) production. Meanwhile, the conventional extra aeration method always causes CO2 stripping and IC loss. Both two reasons limited the algae boosting. Membrane aeration (MA) has the excellent capability of organic carbon thorough degradation and gas blown-off control. In this study, MA-BA was employed to investigate the effect of organic carbon on the algae growth. Results showed that COD had a positive correlation with Chlorophyll- a (Chl- a ) and algae proliferation in MA-BA system according to the redundancy analysis (RDA). The biggest Chl- a concentration (20.95 mg/cm 2 ) occurred in R4 (COD = 400 mg/L). Stimulated algal population changed nutrient removal pathway from bacterial action to algae action. Meantime, Soared algae accumulation would selectively excite the abundance of bacteria that supported the algae growth, such as Acinetobacter, which exhibited a growing trend as the increase of influent COD, especially in the inner biofilm. This paper provided new insight into the effect of organic carbon on the algae in a novel MA-BA system, which will be helpful for future research. Graphical abstract: Image 1 Highlights: The membrane-aerated based bacteria-algae symbiosis system (MA-BA) was proposed. The algae boosted as the increase of COD in MA-BA. Increased COD changed the nutrient removal pathway from bacterial action to algae action. RDA suggested that COD concentration was responsible for the algae growth in MA-BA system.